1998
DOI: 10.1177/019874299802300201
|View full text |Cite
|
Sign up to set email alerts
|

Children who Qualify for LD and SED Programs: Do They Differ in Level of ADHD Symptoms and Comorbid Psychiatric Conditions?

Abstract: Questions have been raised about the implications of the use of the psychiatric diagnosis of attention deficit hyperactivity disorder (ADHD) in the decision process for serving children in special education programs for either learning disabilities (LD) or serious emotional disturbance (SED). In this two-stage study children in LD and SED programs were first screened for ADHD risk using parent and teacher ratings. High-risk students subsequently underwent a comprehensive follow-up assessment for ADHD and comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…There were 28% of students with LD and 65% of students with ED who were reportedly diagnosed with ADHD. These proportions were similar to what Lopez et al (1996) and Schnoes et al (2006) reported, but higher than the rate found by Biederman et al (1996), Bussing et al (1998), Duncan et al (1995), andMcConaughy et al (1994). The high prevalence of ADHD among students with LD or ED might be because many of the symptoms of ADHD resemble those of other disorders, such as LD or ED (Rowland, Lesesne, & Abramowitz, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…There were 28% of students with LD and 65% of students with ED who were reportedly diagnosed with ADHD. These proportions were similar to what Lopez et al (1996) and Schnoes et al (2006) reported, but higher than the rate found by Biederman et al (1996), Bussing et al (1998), Duncan et al (1995), andMcConaughy et al (1994). The high prevalence of ADHD among students with LD or ED might be because many of the symptoms of ADHD resemble those of other disorders, such as LD or ED (Rowland, Lesesne, & Abramowitz, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, among children with LD, prevalence estimates of ADHD range from a low of 16% (Bussing, Zima, Belin, & Forness, 1998) to a high of 31% (Lopez, Forness, MacMillan, Bocian, & Gresham, 1996), with others at around 25% (Barkley, 2006;McConaughy, Mattison, & Peterson, 1994).…”
mentioning
confidence: 99%
“…The prevalence of ODD is nearly identical to that of ADHD (Bussing, Zima, Belin, & Forness, 1998), but, unlike ADHD, it has not been specifically listed as a qualifying condition under a different eligibility category (ADHD has been listed as a condition that may constitute eligibility under the "Other Health Impaired" category). As well, recent trends in service provision indicate tiple regression equations to determine whether participant characteristics systematically predicted respondent decisions.…”
Section: Methods Instrumentationmentioning
confidence: 99%